Exploring Visitor Preferences and Market Potential of a Water-Based Glamping Destination: A Case Study of Danau Paisupok, Banggai Kepulauan - Nanita, Evio Tanti; Nugroho, Rian Abid; Yasin, Mhd Try Imran (CV. Austronesia Akademika, 2025)
This study explores visitor preferences and market potential for the development of a water-based glamping destination at Paisupok Lake, Central Sulawesi, an ecologically unique site characterized by exceptionally clear waters and preserved submerged logs. The research is grounded in the growing global trend toward sustainable, immersive, and comfort-oriented travel experiences, with glamping emerging as a hybrid form of eco-luxury tourism. The primary objective is to assess travelers’ motivations, preferred activities, and facility expectations to inform strategic planning for ecotourism development in the region. A quantitative-descriptive approach was applied through an online survey distributed to 200 purposively sampled respondents aged 20–45 years with prior interest in nature tourism or glamping. Data were analyzed using descriptive statistics and cross-tabulation to examine links between demographics and travel preferences. Findings indicate that key motivations include relaxation, healing, and engagement with ecotourism, with favored activities being canoeing, snorkeling, and lakeside glamping. Respondents emphasized the importance of comfort, privacy, hygiene, and scenic views, while also valuing opportunities for conservation education. Market segmentation highlights a dominant group of young professionals (24–35 years old) with middle-to-upper incomes, positioning the destination within the eco-luxury segment. The study concludes that Paisupok Lake holds strong potential for sustainable glamping tourism by integrating comfort, environmental stewardship, and educational value. Strategic implications underscore the need for tailored short tour packages, storytelling-driven digital promotion, and community-based conservation initiatives to ensure long-term competitiveness and sustainability.